Higher serum bilirubin levels are associated with hemorrhagic transformation after intravenous thrombolysis in acute ischemic Stroke - Chen, Xiaoqing; Yang, Xiangchou; Xu, Xia; Fu, FangWang; Huang, Xiangwei (Frontiers in Aging Neuroscience, 2023)
Background Bilirubin has both antioxidative and prooxidative properties. The study aimed to explore the relationship between serum bilirubin and hemorrhagic transformation (HT) after intravenous thrombolysis in patients with acute ischemic stroke. Methods The patients receiving intravenous thrombolysis with alteplase were retrospectively analyzed. HT was defined as new intracerebral hemorrhage in follow-up computed tomography images within 24–36 h after thrombolysis. Symptomatic intracranial hemorrhage (sICH) was defined as HT accompanied by worsening neurological function. Multivariate logistic regression and spline regression models were performed to investigate the relationship between serum bilirubin levels and the risk of HT and sICH. Results Among 557 included patients, 71 (12.7%) were diagnosed with HT and 28 (5.0%) developed sICH. Patients with HT had significant higher baseline serum total bilirubin, direct bilirubin, and indirect bilirubin levels than those without HT. Multivariable logistic regression analysis indicated that patients with higher serum bilirubin levels, including total bilirubin (OR 1.05, 95% CI 1.01–1.08, p = 0.006), direct bilirubin (OR 1.18, 95% CI 1.05–1.31, p = 0.004), and indirect bilirubin (OR 1.06, 95% CI 1.02–1.10, p = 0.005) had increased risk of HT. Furthermore, multiple-adjusted spline regression models excluded nonlinear association between serum bilirubin levels and HT (p > 0.05 for nonlinearity). Similar results were present between serum bilirubin and sICH. Conclusion The data showed the positively linearly relationship between serum bilirubin levels and the risk of HT and sICH in patients with acute ischemic stroke undergoing intravenous thrombolysis.